JAPJEE: The Sikh Morning Prayer - Mohinder Singh and others; Singh (Mohinder); KALRA (Aneeta) (New Delhi Himalayan Books, 2004)
Lavishly produced with many illustrations and beautiful colors. Japjee is considered the most important prayer of the Sikhs. Meant for recitation in the early hours of the morning-amrit vela-or the ambrosial hour-the Japjee is Guru Nanak's most significant gift to the world of spiritual thought. Guru Arjan Dev, the fifith Guru, rightly gave it the place of honour when he compile the Adi Granth. Contains Punjabi with English translations.
Keywords: Sikhism; religion; Spiritual life--Sikhism